Understanding halal entrepreneurship: concepts and essentiality - Abdullah, Moha Asri (2020)
There is tremendous interest in entrepreneurship in Malaysia, and around the world. Over the past few years, many individuals, as well as families, are actively engaged with the small business. Halalpreneurship is a newly developed concept that has not been fully understood nor widely known as yet. It links halal development to business activities that are executed as Halalpreneurial. It involves all of the functions, events, and actions associated with the perception of opportunities and the creation of organizations to pursue them. The halal entrepreneurial process is a complex phenomenon; however, this process is important in understanding Halalpreneurial growth.